Moderasi beragama dan trauma konflik komunal: Eksplorasi pemahaman dan pengembangan model bagi remaja Kristen di kota Ambon - Jenne Jessica Revanda Pieter; Martha Marselina Patty; Aleta Apriliana Ruimassa; Ricardo Freedom Nanuru (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
Christian adolescents who survived communal conflict in Ambon have grown up within narratives of religiously based violence while living in a digital era susceptible to the spread of radicalism and hate speech. This reality underscores the urgent need to cultivate religious moderation in a structured, context-specific manner. This study aims to explore how Christian adolescent survivors of communal conflict in Ambon understand religious moderation and to develop a relevant model of religious moderation for them. A qualitative case study method was employed, with in-depth interviews conducted with 23 adolescent informants. Findings reveal that their understanding of religious moderation remains normative and incomplete, as trauma from communal conflict has generated negative perceptions toward adherents of other religions. Drawing on these findings, the researchers developed a religious moderation model grounded in Jack Mezirow's Transformative Education theory, encompassing four stages: experience, critical reflection, reflective discourse, and action. This model integrates trauma healing with the formation of a moderate character and can be implemented through Christian churches and schools in post-conflict Ambon. Abstrak Remaja Kristen penyintas konflik komunal di Ambon bertumbuh dalam narasi kekerasan berbasis agama sekaligus terpapar dunia digital yang rentan menyebarkan radikalisme dan ujaran kebencian. Realitas ini menegaskan urgensi penanaman moderasi beragama secara terstruktur dan kontekstual bagi mereka. Penelitian ini bertujuan menggali pemahaman remaja Kristen penyintas konflik komunal di Ambon tentang moderasi beragama serta mengembangkan model moderasi beragama yang relevan dengan konteksnya. Metode yang digunakan adalah penelitian kualitatif studi kasus dengan wawancara terhadap 23 informan remaja. Temuan penelitian menunjukkan bahwa pemahaman informan tentang moderasi beragama masih bersifat normatif dan belum terbentuk secara utuh, karena trauma akibat konflik komunal memunculkan persepsi negatif terhadap pemeluk agama lain. Berdasarkan temuan ini, peneliti mengembangkan model moderasi beragama yang mengacu pada teori pendidikan transformatif Jack Mezirow yang mencakup empat tahapan: pengalaman, refleksi kritis, diskursus reflektif, dan aksi. Model ini mengintegrasikan pemulihan trauma dengan pembentukan karakter moderat dan dapat diimplementasikan melalui gereja dan sekolah Kristen di Kota Ambon pascakonflik.